Lipoprotein lipase expression in unmutated CLL patients is the consequence of a demethylation process induced by the microenvironment - Moreno, P. (2013)
We have previously demonstrated that lipoprotein lipase (LPL) is associated to an unmutated immunoglobulin profile and clinical poor outcome in Chronic Lymphocytic Leukemia (CLL). Despite the usefulness of LPL for CLL prognosis, its functional role and the molecular mechanism regulating its expression remain elusive. Since interaction of CLL B-cells with tissue microenvironment favors disease progression by promoting malignant B-cell growth and considering that tissue methylation can be altered by environmental factors, we investigated the methylation status of LPL gene and the possibility that its over-expression could be associated to microenvironment signals. By comparing methylation changes in the LPL-CpG island between unmutated and mutated CLL patients, we could demonstrate a clear association between LPL expression and a demethylation process in the CpG island near the promoter region of the LPL gene. This process can be induced by proliferative and specific stimuli,particularly we found that CLL B-cell activation through the CD40 plus IL-4 pathway led to LPL expression and gene demethylation in LPL negative CLL samples. Overall, these results suggest that an epigenetic mechanism, triggered by the microenvironment, regulates LPL expression in CLL cells.